The Making Available Right: Problems with “the Public” - Foong, Cheryl (Springer, 2018)
In recent years, we have seen developments in networked technologies such as cloud storage throw the spotlight on the exclusive right of the copyright owner to communicate copyright material to the public. Since its introduction through the WIPO Internet Treaties, the right to communicate to the public by “making available” has promised to take centre stage in the Internet era we now inhabit. However, it has not been until recent times that its scope and impact has come under close scrutiny. The purpose of this chapter is to review the elements and operation of the making available right, focusing in particular on the increasingly problematic notion of “the public”. It will analyse the pitfalls of a judicial trend, spanning several jurisdictions, that exhibits an expansive interpretation of the element. This trend is found in recent cases, and is further illuminated by an analysis of historical cases. This chapter posits that an approach to copyright that takes into account its communications function—to promote the dissemination of knowledge and culture—would bring a deeper level of understanding and balance to the issues at hand.